Strategi Pemasaran Usaha Mikro Kecil Dan Menengah Di Desa Taba Pasmah Kecamatan Talang Empat Kabupaten Bengkulu Tengah - Purwasih, Ira; Nopriansyah, Sendi; Marleza, Yozi; Anggriani, Ida (Jurnal Dehasen Mengabdi, 2024)
The Final Report of the Thematic KKN Group Work Program of Dehasen University Bengkulu in Taba Pasmah Village, Talang Empat District, Central Bengkulu Regency entitled "Strategies to Increase Sales of Micro, Small and Medium Enterprises in Taba Pasmah Village, Talang Empat District, Central Bengkulu Regency". This report discusses the marketing strategies implemented by Micro, Small and Medium Enterprises (MSMEs) in Taba Pasmah Village, Talang Empat District, Central Bengkulu Regency. In this report, the author identifies several problems faced by MSMEs, such as ineffective marketing strategies, limited access to market information, and fluctuations in raw material prices.To overcome these problems, the author recommends several strategies, such as improving product quality, implementing an effective delivery system, and improving communication with customers. This research is expected to contribute to the development of MSMEs in the area and improve the ability of businesses to market their products. In addition, this report is also expected to be a reference for other researchers who want to conduct similar research in the future.